2021
DOI: 10.1371/journal.pone.0246211
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the metabolic side-effects of the second-generation antipsychotic drugs risperidone and paliperidone in animal models

Abstract: Background The second generation antipsychotic drugs represent the most common form of pharmacotherapy for schizophrenia disorders. It is now well established that most of the second generation drugs cause metabolic side-effects. Risperidone and its active metabolite paliperidone (9-hydroxyrisperidone) are two commonly used antipsychotic drugs with moderate metabolic liability. However, there is a dearth of preclinical data that directly compares the metabolic effects of these two drugs, using sophisticated ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 95 publications
1
6
0
Order By: Relevance
“…None of the groups in the high calorie diet group differed from each other. The normal diet group exhibited the typical pattern of glucose clearance observed in non-obese Sprague-Dawley rats [e.g., as observed in our laboratory ( 35 )], with mildly elevated glucose levels at 1 h after glucose challenge, and a return to baseline levels by 2 h.…”
Section: Resultssupporting
confidence: 52%
“…None of the groups in the high calorie diet group differed from each other. The normal diet group exhibited the typical pattern of glucose clearance observed in non-obese Sprague-Dawley rats [e.g., as observed in our laboratory ( 35 )], with mildly elevated glucose levels at 1 h after glucose challenge, and a return to baseline levels by 2 h.…”
Section: Resultssupporting
confidence: 52%
“…Regarding the drug's mechanisms of action, these agents are primarily D2 antagonists, whereas additional properties may include 5-HT2A antagonism and 5-HT1A agonism [12]. Though more effective compared to other atypical antipsychotics on average, olanzapine's side effects may be relatively more severe compared to those of other second-generation antipsychotics [13,14]. In our case, the patient experienced significant treatment adverse events.…”
Section: Discussionmentioning
confidence: 90%
“…Boyda et al reported insulin resistance during paliperidone-induced hyperglycemia. 19) Furthermore, insulin resistance has been implicated in the regulation of AMPK. 20) These findings suggest that the single administration of paliperidone induced insulin resistance.…”
Section: Discussionmentioning
confidence: 99%